Pengaruh Manajemen Mutu Dalam Meningkatkan Profesionalisme Guru Di Madrasah Tsanawiyah Al-Ikhlas Setungkep - Syahdan; Ittihad; Apriawan (Pendidikan Al-Gafari, 2023)
Management quality is often called TQM (Total Quality Management), namely something tool For increasing something product. Teacher professionalism is performance quality, the teacher is a worker profession, Therefore They must uphold high professionalism. In case this TQM is used To increase quality or teacher's abilities to operate his task in other words, become a professional teacher. Study This aim is to know if variable X (Quality Management) has a significant influence on variable Y (Teacher Professionalism). Type of research This is a quantitative study, namely the data used in the study This form numbers. Deep sample study These are teachers at MTs Al-Ikhlas Setungkep, totaling 20 respondents, using cluster sampling technique (area sampling). Data retrieved use a questionnaire and supported with observation data and documentation. Data is processed with SPSS version 20 for Windows with method instrument test analysis, analysis regression simple, and hypothesis testing. The partial test results (t-test) show mark significance 0.268>0.05 meaning variable influence management quality No influential significance to teacher professionalism. Whereas the R square value of 0.068 or 6.8% means variable influence management quality influence teacher professionalism was 6.8%.